Distribution patterns of shallow water polychaetes (Annelida) along the Alexandria coast, Egypt (eastern Mediterranean) - DORGHAM, M. M.; HAMDY, R.; EL RASHIDY, H. H.; ATTA, M. M.; MUSCO, L. (Mediterranean Marine Science, 2014)
Shallow hard bottom and intertidal soft bottom polychaete assemblages of the Alexandria coast, southeastern Mediterranean (Levantine Sea), were studied during a complete annual cycle in order to analyze spatial temporal patterns of variation in assemblages, and relevant factors related to polychaete distribution. The present study recorded a total of 73 species, belonging to Syllidae (22 species), Nereididae (9 species), Serpulidae (6 species), Eunicidae (5 species) and other 19 families. The assemblages experienced pronounced spatial and temporal variation throughout the study area, but spatial variation appeared more important in determining the observed patterns. Polychaete distribution related to variation of grain size and sessile macrobenthos cover suggesting that these structural variables accounted more than the physical-chemical ones (namely BOD, dissolved oxygen, organic carbon, organic matter, salinity, temperature, pH) in influencing the patterns of assemblages’ distribution. The present study is the southeastern-most one dealing with ecology and distribution patterns of hard bottom polychaetes from the Mediterranean Sea, as well as one of the few studies dealing with intertidal soft bottom polychaetes in the Levant Basin.